Cerebellar disturbance in psittacosis. Issue 751 (May 1988) - Shee, C. D.
Abstract : A previously fit man developed psittacosis with marked cerebellar symptoms and signs. He was febrile but not confused, and he responded rapidly to treatment with erythromycin. Even if respiratory symptoms are minimal, psittacosis and other atypical pneumonias should be considered in any patient presenting with fever and cerebellar involvement.